Assistance to the People of Keliling Benteng Hulu Village who were Affected by Floods in Banjar District - Irawanto; Bakhtiar; Muhammad Jamili; Akhmad Riduan; Riky Welli Saputra; Imam Suharto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Keliling Benteng Hulu village, is one of several in the West Martapura sub-district, Banjar Regency, which often experiences natural disasters, especially floods, in the middle of March 2023 this area was flooded, actually the area affected by the flood covers the West Martapura sub-district but in this service activity it is carried out to the community in this village area which includes 65 families. many efforts have been made both from the government and concerned parties to overcome this incident. Community service activities this time aim to minimize the adverse effects of this flood disaster. The results of this service are expected to reduce the impact of flood-affected communities in the form of food aid and medicines.